Supply Chain Management and Supply Chain Performace: The Case of Mcdonald’s - Vanessa Nicole Setiawan; Lena Ellitan (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
McDonald’s is one of the well known fast food restaurant. McDonald’s is known with their complicated supply chain management to make sure all aspects is working to consistently provide quick and fresh food for the customers. But we can’t deny that not every supply chain is perfect, as McDonald’s currently has difficulty in their supply chain because of global shortage of potatoes that affects some of their franchisees. Therefore, this paper aims to examine and understand on how the supply chain management, supply chain drivers, and supply chain performance in McDonald’s work and on how McDonald’s solve the supply chain issue. The result showed that McDonald’s mainly use outsourced third party within their supply chain. Even though, McDonald’s has a very complex supply chain management, it is still considered successful because it allows the huge fast food chain and its suppliers to create value together rather than merely exchanging it. As a result, more beneficial, lasting alliances are formed. McDonald’s use JIT to eliminate cost and reduce waste as their supply chain performance indicator.